Protection of built environment against earthquakes - Dolsek, Matjaz (Springer, 2011)
Observed high losses throughout the world indicate that the risk due to earthquake hazard is still high and that it may even increase due to rapid population growth in the urban areas and ageing process of build environment.Therefore it is important to further develop methods, techniques and tools to achieve more accurate design and better preparedness, which are the key elements for successful protection of build environment against earthquakes.